Phosphorylated Rad18 directs DNA Polymerase η to sites of stalled replication - Day, Tovah A. (The Rockefeller University Press, 2010)
The E3 ubiquitin ligase Rad18 guides DNA Polymerase eta (Polη) to sites of replication fork stalling and mono-ubiquitinates proliferating cell nuclear antigen (PCNA) to facilitate binding of Y family trans-lesion synthesis (TLS) DNA polymerases during TLS. However, it is unclear exactly how Rad18 is regulated in response to DNA damage and how Rad18 activity is coordinated with progression through different phases of the cell cycle. Here we identify Rad18 as a novel substrate of the essential protein kinase Cdc7 (also termed Dbf4/Drf1-dependent Cdc7 kinase [DDK]). A serine cluster in the Polη-binding motif of Rad18 is phosphorylated by DDK. Efficient association of Rad18 with Polη is dependent on DDK and is necessary for redistribution of Polη to sites of replication fork stalling. This is the first demonstration of Rad18 regulation by direct phosphorylation and provides a novel mechanism for integration of S phase progression with postreplication DNA repair to maintain genome stability.